Adsorption behavior and mechanism of Au(III) on caffeic acid functionalized viscose staple fibers. (August 2020) - Liu, Fenglei; Zhou, Liang; Tao, Liyuan; Qian, Ling; Yu, Gang; Deng, Shubo
Abstract: A novel fibrous adsorbent (DAVSF-CA) was synthesized via grafting caffeic acid (CA) onto dialdehyde viscose staple fiber (DAVSF), and used to selectively adsorb Au(III) from simulated wastewater. Fourier Transform Infrared (FTIR), X-ray Photoelectron (XPS) and Nuclear Magnetic Resonance (NMR) spectra confirmed that caffeic acid was successfully grafted on DAVSF through condensation reaction. Adsorption experiments revealed that the adsorption of Au(III) on DAVSF-CA was extremely dependent on pH values and temperatures, and the maximum adsorption capacity of 3.71 mmol/g for Au(III) was obtained at pH 3.0 and 333 K according to the Langmuir fitting. High temperature was favorable for Au(III) adsorption because the adsorption of Au(III) on the DAVSF-CA was endothermic. The competitive adsorption demonstrated that DAVSF-CA had a good preference to Au(III) adsorption in the presence of some coexisting pollutants. The adsorption isotherm data of Au(III) were well-described by the Langmuir model, while the kinetic data were fitted well by the Pseudo-second-order equation. The major reaction involving the reduction of Au(III) to Au(0) was identified by XPS and XRD analysis. Namely, Au(III) was first captured on protonated functional groups via electrostatic adsorption, and then reduced to its elemental form and formed the nano-particles on the adsorbent surfaces. Graphical abstract: Image 1 Highlights: A fibrous DAVSF-CA was successfully prepared via condensation reaction. DAVSF-CA was favorable for Au(III) removal from simulated wastewater. DAVSF-CA exhibited high adsorption capacity of 3.71 mmol/g for Au(III). Adsorption of Au(III) was confirmed to be a reduction-adsorption process.